ANALIS PENERAPAN BALANCE SCORECARD TERHADAP KINERJA PERUSAHAAN PADA PT MALINDO FEEDMILL TBK - Pratiwi; Elok Kurniawati (Fakultas Ekonomi, Universitas Negeri Jakarta, 2019)
This study aims to analyze the development of performance measurement systems at PT Malindo Feedmill Tbk and to find out the application of Balance Scorecard as a performance measurement system at PT Malindo Feedmill Tbk. This performance measurement is seen from a financial and non-financial perspective. This research was obtained from interviews, distributing questionnaires and observations. Data collection uses primary and secondary data. Primary data obtained from respondents of employees and customers of PT Malindo Feedmill Tbk. Secondary data is obtained from the annual report of PT Malindo Feedmill Tbk. Analysis and interpretation of non-financial terms are said to be good. While in terms of nonfinancial, although there is a fluctuation of financial ratios, it can be said to be quite good.